BRIDGING GAPS: ANALYZING FINTECH ADOPTION AND ITS CONTRIBUTION TO OVERCOMING SOCIAL EXCLUSION IN THE INDONESIAN FINANCIAL LANDSCAPE - Muh Fadli Wahyu Utomo; Darwanto Darwanto (EKUITAS (Jurnal Ekonomi dan Keuangan), 2024)
Financial Technology, a component of the technological revolution in the financial industry, has a significant impact on both the micro and macro finance sectors. Significant investment is fueling the growth of the FinTech sector on a global scale. The mobile payment and transfer industry experienced the most rapid growth, increasing by 75% in 2019. Indonesia has emerged as a significant hub for digital economic growth, with 203 million users and a transaction value of US$ 99.1 billion in 2022. Nevertheless, this favorable pattern has yet to affect the Indonesian economy. The extent of financial inclusion in Indonesia remains one of the lowest compared to other nations in ASEAN. This study examines the factors influencing the utilization of FinTech in Indonesia and the resulting impact on financial inclusion. SEM-PLS method was used for quantitative analysis to examine 369 data respondents statistically. The findings of this study indicate that the four underlying factors (digital literacy, financial literacy, acceptance model, and usage of technology) have a favorable and significant impact on the intention to utilize FinTech payments. Sustainable use has also been exploitative and exploratory behavior by users. Using FinTech payments with exploitative and explorative patterns has been statistically demonstrated to enhance financial inclusion in Indonesia.